Exposure to source-specific air pollution in residential areas and its association with dementia incidence: a cohort study in Northern Sweden - Oudin, Anna; Raza, Wasif; Flanagan, Erin; Segersson, David; Jalava, Pasi; Kanninen, Katja M; Rönkkö, Topi; Giugno, Rosalba; Sandström, Thomas; Muala, Ala; Topinka, Jan; Sommar, Johan (Scientific reports, 2024)
The aim of this study was to investigate the relationship between source-specific ambient particulate air pollution concentrations and the incidence of dementia. The study encompassed 70,057 participants from the Västerbotten intervention program cohort in Northern Sweden with a median age of 40 years at baseline. High-resolution dispersion models were employed to estimate source-specific particulate matter (PM) concentrations, such as PM10 and PM2.5 from traffic, exhaust, and biomass (mainly wood) burning, at the residential addresses of each participant. Cox regression models, adjusted for potential confounding factors, were used for the assessment. Over 884,847 person-years of follow-up, 409 incident dementia cases, identified through national registers, were observed. The study population's average exposure to annual mean total PM10 and PM2.5 lag 1-5 years was 9.50 µg/m3 and 5.61 µg/m3, respectively. Increased risks were identified for PM10-Traffic (35% [95% CI 0-82%]) and PM2.5-Exhaust (33% [95% CI - 2 to 79%]) in the second exposure tertile for lag 1-5 years, although no such risks were observed in the third tertile. Interestingly, a negative association was observed between PM2.5-Wood burning and the risk of dementia. In summary, this register-based study did not conclusively establish a strong association between air pollution exposure and the incidence of dementia. While some evidence indicated elevated risks for PM10-Traffic and PM2.5-Exhaust, and conversely, a negative association for PM2.5-Wood burning, no clear exposure-response relationships were evident.
Keywords: Dementia; dospělí; pevné částice; Švédsko; Female; Adult; ženské pohlaví; demence; znečištění ovzduší; lidé; Air Pollution; Particulate Matter; kohortové studie; Incidence; Cohort Studies; Sweden; Male; incidence; Aged; Air Pollutants; vystavení vlivu životního prostředí; lidé středního věku; senioři; mužské pohlaví; látky znečišťující vzduch; Environmental Exposure; Middle Aged; Humans